The Impact of Urban Transport Infrastructure and Its Development on the Users’ Sense of Safety: The Case of Kraków - Świda, Jarosław (Journal of Public Governance, 2023)
Objective: This paper assesses the impact of the new infrastructure in the city of Kraków on the sense of safety of the users of the local transport infrastructure in terms of its growth and influence on the residents’ safety. Research Design & Methods: The research was conducted using questionnaire interviews in a group of 203 respondents in May 2022. Findings: In the respondents’ opinion, Kraków’s transport infrastructure positively impacts their sense of safety, and the solutions introduced to increase road safety have served their purpose. The city’s transport infrastructure for cyclists is regarded as its weakness, while the best safety-related solutions can be observed in the infrastructure for pedestrians. Implications/Recommendations: The expansion of the transport infrastructure in urban areas represents a major factor underpinning the development of spatial structure in cities. A well-functioning urban transport system is a condition sine qua non for the provision of an effective and efficient transportation service for the city’s residents, thus improving broadly understood quality of life. Given a large number of traffic users, the city authorities are under the obligation to ensure that the transport infrastructure is safe for them. The new initiatives and proper infrastructure management help improve the comfort of travel and the quality of life for residents and visitors alike. Contribution/Value Added: This study contributes to academia and practice by offering data and recommendations to improve the safety of users of city infrastructure. Article classification: research article JEL classification: R41